PERAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP PROFITABILITAS DI SEKTOR PERBANKAN INDONESIA - Shofwan; Nurhalida, Salma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Environmental issues have encouraged various parties to carry out efforts to reduce the negative impacts that can arise from these issues that have the potential to hinder environmental sustainability. Business practices that focus on sustainability by incorporating environmental, social and governance aspects are becoming increasingly popular among companies, especially banks. This study aims to analyze the effects of ESG implementation proxied by Green Credit, Corporate Social Responsibility Fund, and Deposit Insurance Premium on bank profitability as measured by ROA (Return on Assets) in 2017-2021 using Bank Size proxied by Total Assets as a control variable. This study uses a quantitative approach by conducting panel data regression analysis to determine the simultaneous effect and partial effect of the independent variables on the dependent variable of the study. The results show that simultaneously all independent variables have a significant impact on bank profitability. Partially, the three ESG proxies have no significant effect on bank profitability, but the Bank Size has a positive impact on bank profitability.